Tanggung Jawab Notaris dalam Penerbitan Covernote atas Permintaan PT Bank Perkreditan Rakyat (BPR) NBP-15 Berastagi - Chatey Margaretha br Singarimbun; Grace Angel Imanuela Sihombing; Debora Irniyesha Manalu; Herman Brahmana (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the responsibility of Notaries in issuing Covernotes at the request of PT Bank Perkreditan Rakyat NBP-15 Berastagi. A Covernote is a temporary statement arising from banking practice, although not explicitly regulated in the Notary Office Act and not an authentic deed. This empirical juridical research shows that a Covernote only serves as an administrative and moral guarantee without perfect evidentiary power. A Notary's liability may arise in administrative, civil, or criminal spheres if negligence or intentional misconduct causing losses is proven. Notaries must apply the prudential principle when issuing them to avoid legal risks.